The Impact of Islamic Financial Deepening on Economic Growth in Indonesia - Anwar, Moh (Universitas Airlangga, 2024)
Indonesia is starting to pay attention to this trending issue to boost national economic growth because Indonesia is still below other countries regarding the development of its financial sector, especially in Islamic finance. This study employs a quantitative research approach, utilizing multiple linear regression analysis, to investigate the influence of various aspects of Islamic finance on Gross Domestic Product (GDP) as an indicator of economic growth in Indonesia. This research is expected to be able to examine in more detail the role model of Islamic financial deepening in Indonesia and how it affects economic growth. Through a comprehensive discussion, we examine the potential impact of Islamic financial instruments, including Murabahah, Mudharabah (Islamic deposit), total assets of Islamic banking, Islamic stock market capitalization, and Islamic stock transaction volume, on economic growth. Findings suggest that while certain components, such as government bonds (sukuk), have a significant positive influence on GDP through infrastructure financing and investor confidence, others, like corporate bonds (sukuk), may have limited direct impact due to their focus on specific corporations rather than broad-based economic growth. This research contributes to the understanding of the role of Islamic finance in Indonesia's economic development and informs policymakers, practitioners, and academics on optimizing its contributions while ensuring financial stability and inclusion.